Synergistic alleviation effects of anchovy hydrolysates-catechin on scopolamine-induced mice memory deficits: the exploration of the potential relationship among gut-brain-axis. Issue 3 (24th January 2022) - Zhao, Tiantian; Zhang, Chen; Zhong, Saiyi; Chen, Qirong; Liu, Shuo; Jiao, Wenjuan; Liu, Weifeng; Huang, Lihua; Zhang, Yehui; Zhang, Yousheng
Abstract : In this study, the regulation of microbiota-metabolites-brain-neurotransmitters axis may be one of the mechanisms for APH-CA against scopolamine induced cognitive deficits. Additionally, the synergic effects of APH and CA were partially confirmed. Abstract : Anchovy protein hydrolysates (APH) and catechin (CA) have proved to be effective in memory improvement. However, the enhancing effects of APH-CA conjugates on the memory are little investigated. The underlying mechanism and synergic effects remain unclear. Herein, relationships among memory enhancement, gut microbiota, fecal metabolites, and neurotransmitters of mice regulated by APH-CA were investigated. APH, APH-CA, and CA decreased MDA, IL-1β, and TNF-α in liver, altered levels of GPx, LDH, IL-1β, and TNF-α in serum, re-structured gut microbiota, regulated fecal metabolites, and regulated neurotransmitters in the brain. The alleviation effects of APH-CA were partially better than those of APH and CA. The 16s rRNA results illustrated that Bacteroidetes and Firmicutes were altered. Notably, memory-related metabolites and neurotransmitters were significantly up-regulated by the administration of samples. Moreover, possible connections are observed among the gut microbiota, fecal metabolites, and brain neurotransmitters. Together, the regulation of the microbiota-metabolites-brain-neurotransmitters axis may be one of the mechanisms for APH-CA against scopolamine-induced cognitive deficits. In addition, the synergic effects of APH and CA were partially confirmed.